Traditional and new methods of pension authentication in China: Reasons, methods and problems - Zh. Liu; V. A. Isaev (Мир новой экономики, 2023)
The article discusses the topic of the digitalization of the pension systems in the People’s Republic of China, the spread of the new social authentication methods and the new pension payment confirmation system in the country. The population ageing problem is forcing the government of the People’s Republic of China to develop new methods of social support for the retired citizens. The article deals with the problems of pension payment confirmation for the Chinese, who are currently abroad, as well as the methods of solving the issue. Special attention is paid to the problem of pension authentication through overseas Chinese multifunctional centers (MFC). The article studies the main positive and negative aspects of “traditional” and “new” methods of pension authentication.